Biosynthesis and functions of sulfur modifications in tRNA - Shigi, Naoki (Frontiers in Genetics, 2014)
Sulfur is an essential element for a variety of cellular constituents in all living organisms. In tRNA molecules, there are many sulfur-containing nucleosides, such as the derivatives of 2‑thiouridine (s2U), 4-thiouridine (s4U), 2-thiocytidine (s2C), and 2-methylthioadenosine (ms2A). Earlier studies established the functions of these modifications for accurate and efficient translation, including proper recognition of the codons in mRNA or stabilization of tRNA structure. In many cases, the biosynthesis of these sulfur modifications starts with cysteine desulfurases, which catalyze the generation of persulfide (an activated form of sulfur) from cysteine. Many sulfur-carrier proteins are responsible for delivering this activated sulfur to each biosynthesis pathway. Finally, specific “modification enzymes” activate target tRNAs and then incorporate sulfur atoms. Intriguingly, the biosynthesis of 2-thiouridine in all domains of life is functionally and evolutionarily related to the ubiquitin-like post-translational modification system of cellular proteins in eukaryotes. This review summarizes the recent characterization of the biosynthesis of sulfur modifications in tRNA and the novel roles of this modification in cellular functions in various model organisms, with a special emphasis on 2-thiouridine derivatives. Each biosynthesis pathway of sulfur-containing molecules is mutually modulated via sulfur trafficking, and 2-thiouridine and codon usage bias have been proposed to control the translation of specific genes.